1998
DOI: 10.2486/indhealth.36.127
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Body Vibration and Health Effects in the Agricultural Machinery Drivers.

Abstract: Recently farm mechanization has been widespread and developing rapidly, in particular riding farm machines are increasingly used in paddy fields in Japan. We have no information available on the actual situation regarding whole-body vibration on the seats of these farm machines from the standpoint of labour protection. Measurement and evaluation of whole-body vibration was performed on the seats of popular riding agricultural machineries. Whole-body vibration on the seats of combine harvesters and wheel tracto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 2 publications
0
20
0
1
Order By: Relevance
“…With prolonged exposure to WBV, the sensory information received from the somatosensory, vestibular, and/or visual systems could lead to postural instability, contributing to an increased risk of fall during egress of the vehicle. While previous research has been instrumental in determining the casual relationship of WBV and postural stability in simulated laboratory environments (uni-axial vibration) (Futatsuka et al, 1998;Martin et al, 1980;Cohen, 1979;Cornelius, 1994;Couch, 1981;Peli et al, 2003;Roll et al, 1980); the lack of available real-time vibration exposure (tri-axial) in LHF truck drivers, leaves a theoretical void in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…With prolonged exposure to WBV, the sensory information received from the somatosensory, vestibular, and/or visual systems could lead to postural instability, contributing to an increased risk of fall during egress of the vehicle. While previous research has been instrumental in determining the casual relationship of WBV and postural stability in simulated laboratory environments (uni-axial vibration) (Futatsuka et al, 1998;Martin et al, 1980;Cohen, 1979;Cornelius, 1994;Couch, 1981;Peli et al, 2003;Roll et al, 1980); the lack of available real-time vibration exposure (tri-axial) in LHF truck drivers, leaves a theoretical void in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Different road surfaces have different effects on WBV 11) . These effects also vary according to the different manufacturers and models of AMDS 11,12) . In addition, the duration of exposure to WBV (T Exp ) fluctuates based on different seasons and different tasks performed.…”
mentioning
confidence: 99%
“…The researches indicated that the reaction time in psychomotor efficiency tests becomes extended by 30-40% at infrasound levels of 115-120 dB. Vehicle drivers exposed to simulated infrasound at levels of 100-135 dB for 15 minutes reported feelings of fatigue, apathy, depression, vibrations of internal organs, loss of concentration, and pressure in the ears [18][19][20][21][22][23][24][25].…”
Section: Results and Disscussionmentioning
confidence: 99%